Kualitas fisik dan pH silase batang semu pisang ambon (Musa paradisiaca var. sapientum (L) Kunt.) yang diberi berbagai jenis starter - Randi Rizaldi; Syifa Nurjannah; Nilawati Widjaja; Hilman Permana; Sari Suryanah (University of Insan Cendekia Mandiri, 2025)
Ambon banana is a type of tree that has a soft stem. One of the by-products of banana trees is the stem. Banana pseudo-stems can be used as animal feed because they contain quite good nutrients and do not contain anti-nutrients. The purpose of the research was to determine the physical quality and pH of Ambon banana pseudo-stem silage given various types of starter. this research used an experimental method and completely randomized design, which used four treatments and five replications. The treatments were P1: 100% banana pseudo-stem + 10% cassava flour, P2: 100% banana pseudo-stem + 10% rice bran, P3: 100% banana pseudo-stem + 10% pollard, P4: 100% banana pseudo-stem + 10% molasses. The observation data wasthen tested by analysis of variance and Duncan further test. The variables observed consisted of physical quality carried out by 15 untrained panelists, and also pH. according to the research results, it can be concluded that different types of starters affected physical quality and pH. P3 treatment with the addition of 10% pollard gave the best results.